Management control in multinational firms: future research directions - Abdullah, Zarifah; Abdul Khalid, Siti Nabiha (Universiti Malaysia Perlis, 2011)
Issue of control in the multinational companies has been very much debated by the scholars in the area of international business.The changes in global competitive environment have lead to changes in the headquarters-subsidiary relationship.Control has been typified less by chain of command, and more by mutual interdependence, and learning.Thus, the issue of control in multinational firms and the future research direction in this area are discussed in this paper.In so doing, the types and forms of prevailing multinational firms and the forms of control are elaborated. The processes of transfers of management practices especially that of management control practices are also discussed in terms the factors influencing the transfer process, the transfer mechanism, and the effects of transfer.